Reimagining Counterstruggle as a Comprehensive Theoretical Framework for Policy Design and Implementation: Dimensions and Factors of Struggle and Resistance - Sergei Khatunov (Journal of Political Science: Bulletin of Yerevan University)
This article analyzes strategic issues related to political factors of counterstruggle, which manifest different dimensions of confrontation, counteraction, opposition and resistance. This stimulates the development of innovative solutions that are actively used by political actors to analyze the economic, social, political situation in countries and regions with transitional political and economic systems, as well as to prepare public opinion for making important political decisions. In this context, political assets can quickly transform into liabilities, and ignored liabilities can become invaluable assets. Existing conceptual frameworks for policymaking fail to effectively address the enormous uncertainty inherent in environmental assessment, especially the complexity of constant, gradual change. The counterstruggle framework offers a more effective approach, mitigating the oversimplifications often found in geopolitical analysis. This framework builds on the trifunctional hypothesis, emphasizing compensatory capacities and the need for a balance between all factors to achieve a given goal. This article analyzes the interplay of space, time, and force within counterstruggle that gives rise to trifunctionality. This provides insight into the adaptive capacity available to navigate uncertainty and change, ultimately contributing to the stability that states and societies seek. The relationship between politics and economics goes far beyond our usual perception, in an inverse correlation influenced by the multiplicative effect of counterstruggle factors. In situations marked by uncertainty, the ability to quickly assess and adapt to the current environment becomes paramount, opening up numerous underappreciated methods of policy research.